2009
DOI: 10.1073/pnas.0812056106
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast excited-state isomerization in phytochrome revealed by femtosecond stimulated Raman spectroscopy

Abstract: Photochemical interconversion between the red-absorbing (Pr) and the far-red-absorbing (P fr) forms of the photosensory protein phytochrome initiates signal transduction in bacteria and higher plants. The Pr-to-Pfr transition commences with a rapid Z-to-E photoisomerization at the C 15AC16 methine bridge of the bilin prosthetic group. Here, we use femtosecond stimulated Raman spectroscopy to probe the structural changes of the phycocyanobilin chromophore within phytochrome Cph1 on the ultrafast time scale. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
291
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(332 citation statements)
references
References 29 publications
27
291
3
Order By: Relevance
“…In the Pr state, a substantial portion of the net positive charge is delocalized on the two inner rings B and C (43) (Fig. 4 A and B), whereas in the Pfr state, ring D carries the partial positive charge (16) (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Pr state, a substantial portion of the net positive charge is delocalized on the two inner rings B and C (43) (Fig. 4 A and B), whereas in the Pfr state, ring D carries the partial positive charge (16) (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Early NMR spectroscopic studies on proteolytic phytochrome fragments (12,13) indicated that this isomerization occurs at the C15═C16 double bond (for numbering, see Fig. 1A), a geometrical change in line with vibrational spectroscopic investigations (14)(15)(16) and results from recent 13 C solid-state NMR (17,18) in which the most significant changes during the light-triggered conversions are confined to rings C and D. Exact geometries of the chromophore in the Pr state have been resolved as periplanar ZZZssa configurations in bacteriophytochromes from Deinococcus radiodurans (19) and Rhodopseudomonas palustris (20) as well as in the more plant-phytochrome-like Cph1 from the cyanobacterium Synechocystis 6803 (21). On the other hand, the crystal structure of the unusual bacteriophytochrome PaBphP Pseudomonas aeruginosa (22) whose ground state is Pfr shows a ZZEssa conformation, consistent with the expected primary photochemistry at the C15═C16 double bond (Fig.…”
mentioning
confidence: 99%
“…However, other studies suggest that the multiexponential relaxation rate reflects the influence of sequential intermediate states following photoexcitation (2,4). In this interpretation, heterogeneity in the equilibrium system is unrelated to the distribution of isomerization rates (i.e., the reaction dynamics are homogeneous within the ensemble).…”
mentioning
confidence: 90%
“…Femtosecond laser spectroscopies conducted in recent years show that the isomerization dynamics of bilin cofactors in bacteriophytochromes span timescales of hundreds of femtoseconds to hundreds of picoseconds (2)(3)(4)(5)(6). The origin of this broad distribution in rate constants has been a matter of debate.…”
mentioning
confidence: 99%
“…A complementary Raman spectroscopy study concluded that 85% of the molecules relax back from the excited P r * state to the P r ground state explaining the low quantum yield of phytochrome phototransformation. After isomerization, the residual 15% were supposed to reach a product-like electronically excited Lumi-R* state that decays to the Lumi-R ground state, which is formed within 30 ps (26). Recent multipulse pump-probe data indicate that isomerization proceeds, most likely via a conventional conical intersection, between the excited and ground state energy surfaces (27).…”
Section: Photoconversion Of Syncph2(1-2) a Pas-less Phytochrome-mentioning
confidence: 99%